The careful mother also enters her little angels: infant mortality in Piauí (1889-1945) (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: The purpose of this article is to analyse how mothers started to play a central role in the observation of medical instructions on the preservation of health and treatment of illness among their children in Piauí between 1889 and 1945. This was aimed at confronting the high indices of the child obituary, consistent with the process of valuing the child as wealth of the country. For that were used, medical magazines, newspapers, medical sources and the state government.Keywords: History. State. Doctors. Mothers. Child mortality.